2019
DOI: 10.1002/phar.2312
|View full text |Cite
|
Sign up to set email alerts
|

Association between Use of Methadone, Other Central Nervous System Depressants, and QTc Interval–Prolonging Medications and Risk of Mortality in a Large Cohort of Women Living with or at Risk for Human Immunodeficiency Virus Infection

Abstract: STUDY OBJECTIVE To evaluate the association between use of methadone, other central nervous system (CNS) depressants, and QTc interval-prolonging medications and risk of mortality among human immunodeficiency virus (HIV)-infected and at-risk HIV-uninfected women. DESIGN Multicenter, prospective, observational cohort study (Women's Interagency HIV Study [WIHS]). PARTICIPANTS A total of 4150 women enrolled in the WIHS study between 1994 and 2014 who were infected (3119 women) or not infected (1031 women) with HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, while methadone increased the odds for prolonged QTc (OR 4.58, CI 1.41, 14.9), antiretroviral therapy decreased the odds (OR 0.35, CI 0.13, 0.96) [132]. Further, a recent prospective cohort study found that QTc-prolonging medications were associated with an increased risk of mortality in women with HIV (HR 1.15 per drug, 95% CI 1.00-1.33) [133].…”
Section: Non-aids-definingmentioning
confidence: 99%
“…However, while methadone increased the odds for prolonged QTc (OR 4.58, CI 1.41, 14.9), antiretroviral therapy decreased the odds (OR 0.35, CI 0.13, 0.96) [132]. Further, a recent prospective cohort study found that QTc-prolonging medications were associated with an increased risk of mortality in women with HIV (HR 1.15 per drug, 95% CI 1.00-1.33) [133].…”
Section: Non-aids-definingmentioning
confidence: 99%